CASIMIR LEWY: A FORGOTTEN POLISH ANALYTIC PHILOSOPHER FROM CAMBRIDGE - Brewer, Marta (Hybris, 2025)
Casimir Lewy (1919 – 1991) was an analytical philosopher born and raised in Poland, who worked and taught at the University of Cambridge. He left behind one book, Meaning and Modality published in 1976, as well as more than a dozen articles and reviews. He was remembered by his students as an exceptional teacher. This article is a reflection on whether Lewy should be called a forgotten philosopher, who perhaps deserves to be considered more widely as a Polish contributor to the advancements in analytic philosophy. To this end, the author presents and analyses 15 articles by Lewy published between 1937 and 1964, which are divided into four thematic categories: topics related to the justification of empirical propositions, epistemological topics other than justification, semiotics, and problems in the area of logic or set theory.